PERKEMBANGAN PONDOK PESANTREN SAFINATUSSALAMAH DI DESA MARPUNGE KECAMATAN PUTRI BETUNG KABUPATEN GAYO LUES TAHUN 2007-2020 - FARIDA HUSNA; SANI SAFITRI; SYARIFUDDIN SYARIFUDDIN (Raudhah - Proud To Be Professional, 2022)
This study examines the background of the establishment of the Safinatussalamah Islamic boarding school and the development of the Safinatussalamah Islamic Boarding school in Marpunge Village, Putri Betung District, Gayo Lues Regency. The method used in this research is the historical method which has four stages, namely the first heuristic which is useful for being able to find information or sources regarding the regarding the research, the second is source criticism which is used to examine sources more deeply, the third is interpretation which in this case interprets the source that have been obtained and the fourth is historiography which is the last stage in the study to write a report on the final results of the research. The results showed that the Safinatussalamah Islamic Boarding school is a boarding school located in Marpunge village, this boarding school was established with the intention to spread Islamic teachings and continue the stuggle of the ulama in spreading Islam and was successfully established in 2007, furthermore the development of Islamic boarding schools can be seen from 2007-2020, this development wiil go through several aspects, namely: students, educators, infrastructure and Islamic boarding school curriculum.